Improvement of Adaptive Cruise Control Performance. (14th September 2010) - Miyata Miyata, Shigeharu Shigeharu; Nakagami Nakagami, Takashi Takashi; Kobayashi Kobayashi, Sei Sei; Izumi Izumi, Tomoji Tomoji; Naito Naito, Hisayoshi Hisayoshi; Yanou Yanou, Akira Akira; Nakamura Nakamura, Hitomi Hitomi; Takehara Takehara, Shin Shin
Abstract : This paper describes the Adaptive Cruise Control system (ACC), a system which reduces the driving burden on the driver. The ACC system primarily supports four driving modes on the road and controls the acceleration and deceleration of the vehicle in order to maintain a set speed or to avoid a crash. This paper proposes more accurate methods of detecting the preceding vehicle by radar while cornering, with consideration for the vehicle sideslip angle, and also of controlling the distance between vehicles. By making full use of the proposed identification logic for preceding vehicles and path estimation logic, an improvement in driving stability was achieved.